A case of nasopharyngeal angiofibroma removed using a minimally invasive endoscopic endonasal technique - Ji Sun Kim; Dong-Hyun Kim; Eun-Ju Jeon; Byung Guk Kim (Videosurgery and Other Miniinvasive Techniques)
Nasopharyngeal angiofibroma is a rare head and neck tumor characterized by hypervascularity. With the development of various surgical devices and hemostatic agents, endoscopic endonasal surgery for nasopharyngeal angiofibroma, which is characterized by significant intraoperative bleeding, has become possible. We describe our experiences performing an effective endoscopic endonasal removal of a nasopharyngeal angiofibroma without embolization, using advanced devices and hemostatic agents. A 21-year-old male patient presented with massive epistaxis. The characteristic findings of angiofibroma were confirmed by computed tomography scan and nasal endoscopy. Navigation-guided endoscopic endonasal surgery was performed, and complementary devices and products were used to effectively remove the mass. Development of navigation, endoscopes, tissue handling devices, and hemostatic agents has enabled effective endoscopic endonasal removal of nasopharyngeal angiofibroma without embolization.